The Na, K-ATPase alpha3-isoform specifically localizes in the Schmidt-Lanterman incisures of human nerve - Rigoard, P.; Tartarin, F.; Buffenoir, K.; Chaillou, M.; Fares, M.; D'Houtaud, S.; Wager, M.; Giot, J.P.; Quellard, N.; Fernandez, B.; Lapierre, F.; Maixent, J.M. (Cellular and Molecular Biology, 2007)
To our knowledge, there is little reference in literature with regards to alpha3-isoform of Na+,K+-ATPase in human peripheral nerves. The aim of this study was to determine the expression of the neuronal alpha3-isoform of Na+,K+-ATPase in human sural nerves from patients with a permanent medullary central nervous system injury. We studied the immunolocalization of alpha3-isoform of Na+,K+-ATPase using a polyclonal antibody against the amino sequence near the phosphorylation site of the alpha3-isoforms of Na+,K+-ATPase using immunohistochemistry and confocal laser scanning microscopy. An antibody specific for alpha2-isoform of Na+,K+-ATPase was used to label the Schwann cells. Morphometric analysis of longitudinal section of human sural nerves showed that the alpha3-isoform of Na+,K+-ATPase was distributed along the length of axolemma. The myelin sheath of the Schwann cells showed clearly a distribution of alpha3- but not alpha2-isoforms of Na+,K+-ATPase at the level of Schmidt-Lanterman incisures. The human sural nerve shows a specific localization of the Na+,K+-ATPase alpha3-isoform in the Schmidt-Lanterman incisures of Schwann cells in addition to its localization in axonal membranes.